Advanced thermodynamic analysis on exergy flow grafs - Nikulshin, Vladimir; Denysova, Alla; Denysova, Anastasiia (NTU "KhPI", 2017)
In the paper has been proposed f general approach for thermodynamic analysis of systems with arbitrary structures. Method was based on construction and analysis of a new type of exergy- topological model – exergy flow graph and allowed to improve the efficiency of energy intensive systems. The efficiency improving is very important problem and the main way of it solving was through thermodynamic analysis and optimization. It was shown that the processes taking place in the complex energy intensive systems were characterized by mutual transformation of quality different power resources. It has been found that one of the most effective mathematical methods used for exergetic analysis and optimization was the method the method of graph theory. The benefit of graph models can also be demonstrated by its flexibility and vide varieties of possible applications. It has been demonstrated the application of suggested approach for thermodynamic analysis of gas-turbine installation. It has been found that the degree of thermodynamic perfection of turbines and turbocompressors are sufficiently high. Usually, the bigger was the difference between average parameters of the working fluid and the environment, the smaller was the exergy losses. The same situation was also true for heat exchangers. High temperature level in regenerative refrigerator, as compared with intermediate refrigerator, give a higher degree of thermodynamic perfection of the heat exchanger. Exergy losses in other elements of the system were caused by dissipation of the flow transport in the pipelines or by mechanical losses. It has been found that for the system as a whole the degree of thermodynamic perfection was less than the same characteristics for any element of the system in result of the mutual influence of the element on the other in the system.

У статті запропоновано загальний підхід для термодинамічної аналізу систем довільної структури. Метод заснований на побудові і аналізі нового виду ексергією-топологічної моделі – ексергетичному потоковому графі і дозволив підвищити ефективність енерго-інтенсивних систем. Було показано, що процеси, які відбуваються в складних енерго-інтенсивних системах, характеризувалися взаємним перетворенням якісно різних енергетичних ресурсів. Тому термодинамічний аналіз цих систем вимагав спільного застосування обох законів термодинаміки, і, отже, ексергетичного підходу. Було показано, що одним з найбільш ефективних математичних методів, використовуваних при ексергетичної аналізі та оптимізації був метод теорії графів. Перевага графових моделей може бути також продемонстровано шляхом широкої різноманітності їх можливих додатків. Було продемонстровано застосування запропонованого підходу для термодинамічної аналізу газотурбінної установки. Було показано, що ступеня термодинамічної досконалості турбін і турбокомпресорів досить високі. Зазвичай, чим більшою була різниця між середніми параметрами робочого тіла і навколишнього середовища, тим меншими були втрати ексергії. Та ж ситуація була також вірна і для теплообмінників. Більш високий температурний рівень в регенеративної теплообміннику, в порівнянні з проміжним холодильником, та л вищу ступінь термодинамічної досконалості теплообмінника. Втрати ексергії в інших елементах системи були викликані диссипацией транспорту потоку в трубах, або механічними втратами. Було показано, що для системи в цілому ступінь термодинамічної досконалості була менше, ніж для будь-якого елемента системи через взаємного впливу елементів один на одного в системі.
Розширений термодинамічний аналіз ексергетичних потокових графів
Keywords: thermodynamic analysis; topological model; exergy flow graph; arbitrary structures; optimization; аналіз термодинамічний; модель топологічна; граф енергетичний; граф потоковий; структура довільна; оптимізація